2020
DOI: 10.3390/su122410416
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Price in Poland’s Carp Market

Abstract: Poland is one of Europe’s key carp producers. However, its main consumption (80–90% of sales) is concentrated during the Christmas period. In addition, the marginal sale of fish outside the core season does not allow producers to extend the period for generating revenues. Price is one of the essential factors for determining the behavior of both producers and consumers. In this context, our research addressed the role of price on Poland’s carp market, approaching it as a specific product due to its nature and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The research has shown that it is not price that is the main obstacle to consumption, as the demand for carp is rigid. This means that lowering the price will not reflect in an increase in carp demand [ 18 ].…”
Section: The Importance Of Carp In the Food Economymentioning
confidence: 99%
See 1 more Smart Citation
“…The research has shown that it is not price that is the main obstacle to consumption, as the demand for carp is rigid. This means that lowering the price will not reflect in an increase in carp demand [ 18 ].…”
Section: The Importance Of Carp In the Food Economymentioning
confidence: 99%
“…There is also a slow change in consumer orientation on the food market from a quantitative to a qualitative approach, which is exemplified by the diminishing role of price in making decisions about food purchases [ 18 ]. In recent years, there has also been a dynamic increase in the number of Polish consumers who are looking for high-quality products with high nutritional value, produced using methods consistent with the idea of sustainable development, including organic food, produced locally and sold in short supply chains [ 37 ].…”
Section: New Consumer Trends In the Agri-food Sectormentioning
confidence: 99%
“…Becheva et al (2019).21 Raftowicz et al (2020).22 Struś et al (2020).23 Ardakani, Bartolini, Brunori (2020);Solarz et al (2023).24 Ministry of Agriculture and Rural Development (2019).…”
mentioning
confidence: 99%